Pengembangan Buku Saku Digital Berbasis Etnosains di Sekolah Dasar Kota Singkawang - Emi Sulistri; Eti Sunarsih; Erdi Guna Utama (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
This study aims to produce a digital pocket book based on ethnoscience in science subject of heat matter and its transfer which is feasible and interesting to use by students in Singkawang City. The method in this research is development research with the ADDIE model research procedure. The sample at the implementation stage consisted of 31 PGSD STKIP Singkawang students and 141 grade V students at three singkawang city public elementary schools. Data collection techniques in this study consisted of interviews, validation, and questionnaires. The data analysis technique was in the form of a descriptive analysis of scores obtained from the validation results of experts, practitioners and response questionnaires. The results of the research for each stage obtained that the implentation stage was carried out by small-scale trials on the linguistic aspect reached 3.31, large-scale trials reached 3.46. For the material and graphic aspects of the small-scale trial, each had a value of 3.23 and 3.22 in the attractive criteria. Whereas in the large-scale trial each had a value of 3.33 and 3.39 in the very attractive category. It means that ethnosaians-based digital pocketbooks are in general easy to understand and interesting to use because they have a new appearance concept that is coherently integrated with local culture and design according to development.